2021
DOI: 10.3389/fpsyg.2021.792004
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Self, Australian Other: Chinese as a Foreign Language Teacher Identity Construction in Australian Contexts

Abstract: Research in the field of Chinese as a foreign language (CFL) education has been increasing in the past decades. However, the number of studies on CFL teacher identity is limited. To bridge the gap, this study employed a qualitative method to explore Chinese CFL teachers’ identity formation and reformation in Australian contexts. A Chinese-Australian language program was studied to examine the challenges, struggles and developments of Chinese CFL teachers who came to Australia to pursue professional growth. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Whereas, if affordances are challenges to novice CFL teachers, it may weaken their teacher identity construction. This echoes the existing literature that teachers may face various opportunities and challenges in the process of their Chinese language teacher identity construction in an overseas context (e.g., Moloney and Xu, 2015;Han and Ji, 2021;Sun, 2021). Moreover, the present study enriches the literature by extending the affordance perspective to the examination of teachers' identity construction.…”
Section: Positive Role Of Affordances In Novice Cfl Teachers' Identit...supporting
confidence: 81%
See 3 more Smart Citations
“…Whereas, if affordances are challenges to novice CFL teachers, it may weaken their teacher identity construction. This echoes the existing literature that teachers may face various opportunities and challenges in the process of their Chinese language teacher identity construction in an overseas context (e.g., Moloney and Xu, 2015;Han and Ji, 2021;Sun, 2021). Moreover, the present study enriches the literature by extending the affordance perspective to the examination of teachers' identity construction.…”
Section: Positive Role Of Affordances In Novice Cfl Teachers' Identit...supporting
confidence: 81%
“…The above positioning findings add evidence to the literature that self-positioning (i.e., reflexive positioning) and being positioned (i.e., interactive positioning) can help make sense of how different positions experienced by teachers may influence their teacher identity construction (Soreide, 2006). Specifically, our study echoes Han and Ji (2021), showing that the inconsistency between being positioned and self-positioning identities may shake novice CFL teachers' identity construction. For example, our study revealed that there was a conflict between selfpositioning as professionally trained Chinese language teachers and being positioned as outsiders and illegitimate teachers.…”
Section: Double-edged Role Of Positioning In Novice Cfl Teachers' Ide...supporting
confidence: 76%
See 2 more Smart Citations
“…language teachers should have the ability to spread traditional Chinese values, such as respecting the family, treating others politely, and being filial to parents. They can convey these values to students through stories, cases, and discussions, and guide them to implement them in their daily lives [4] .Chinese language teachers can promote Chinese art and literary works by organizing artistic performances, exhibitions, and competitions, guiding students to appreciate traditional Chinese music, dance, opera, and other forms of art, and encouraging them to participate in related activities to enhance their understanding and appreciation of Chinese art and literature. By setting reasonable goals and taking corresponding expansion measures, Chinese language teachers can enhance their cultural dissemination ability, stimulate students' interest and love for Chinese culture, and promote cultural exchange and cooperation between China and Thailand.…”
Section: Reasonable Goals and Ideas For Cultivating Cultural Communic...mentioning
confidence: 99%